The iPad for photographers : master the newest tool in your camera bag - Carlson, Jeff (Peachpit Press, 2012)
The iPad Has Earned a Place in Your Camera Bag! Apple's popular iPad tablet is an incredibly useful tool for photographers on the go. Instead of hauling a laptop on the road or to a photo shoot, you can tuck the lightweight iPad in your camera bag and take advantage of its large screen, third-party apps, and online access to effectively complete and share your work. Novice to pro shooters will discover everything that the iPad has to offer with simple step-by-step instructions and real-world advice for: Importing and copying photos from memory cards using the iPad Camera Connection Kit, then uploading and backing up to iCloud Photo Stream or Dropbox. Organizing and rating images and assigning tags in the field, and integrating them later with Adobe Photoshop Lightroom on your computer. Editing photos with Photogene, Snapseed, and other image adjustment tools. Editing video clips in iMovie, creating slideshows, rough cuts, and more. Using portfolio software to create and deliver impressive iPad presentations for prospective clients. Photographers will learn other clever uses for iPads including triggering the camera shutter remotely, using the screen as a fill flash, calculating depth of field, tracking outdoor light conditions, storing camera manuals as PDFs for quick reference, and other handy at-your-fingertip resources to complement your particular shooting style. A bonus online chapter with additional coverage for the new iPad - including iPhoto and Photoshop Touch apps - is included with purchase. The iPad is a powerful photography tool and this guide will help every photographer take advantages of its full capabilities!